Analysis of intellectual disability students' learning profiles on electron configuration material using individual education - Dian Novita; Egi Rahman Permadi; Khurrotul Aini; Moniqsa Purbo Syahrani; Rusmini (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2025)
This research is motivated by the need for effective learning strategies for students with intellectual disabilities, particularly those who experience cognitive barriers. This study aims to analyze the learning profiles and outcomes of students with intellectual disabilities in relation to electron configuration materials, utilizing individualized educational learning strategies. The learning media developed is the E-LAPD (Electronic-based Student Activity Sheet), integrated through the LiveWorksheet platform. This study employs a mixed-methods research approach, a method that combines quantitative and qualitative methods. The population of this study is three students with intellectual disabilities at SMAN 10 Surabaya. The sampling technique is a saturated sample (total sampling), where the entire population is used as a research sample. Data collection techniques through test and interview methods. The test results were analyzed quantitatively, while the interview results were analyzed qualitatively using the NVivo application. The results indicate that this study can enhance the learning outcomes of students with intellectual disabilities, as evidenced by the posttest scores, which are higher than the pretest scores. Thus, this research is important in helping students with intellectual disabilities and is expected to be the basis for developing more inclusive and adaptive learning media.